Kelainan Refraksi Mata pada Anak - Saiyang, Bella; Rares, Laya M.; Supit, Wenny P. (Medical Scope Journal, 2021)
Abstract: Refractive errors (ametropia) is caused by abnormality of the axial length or abnormality of refractive power of the eye. In children, refractive errors could cause blindness dure to lack of family attention. This study was aimed to obtain the general view of refractive errors among children. This was a literature review study using data of Google Search, ClinicalKey, and Google Scholar. Data were selected based on inclusion and exclusion criteria. There were 10 literatures selected, consisting of 2 case control studies and 8 cross-sectional studies. The results showed that refractive errors in children -myopia, hypermetropia, and astigmatism- were increasing not only in Indonesia. Refractive errors in children were classified according to sex and age with different disorders. Each child was examined by using gold standar. In conclusion, refractive errors in children were myopia, hypermetropia, and astigmatism. There was no significant difference between male and female. In children, studies of various age groups ranging from elementary to high school. This disorder could also occur based on the childrenâ€™s activities, therefore, family attention was really needed.Keywords: refractive errors, childrenÂ Abstrak: Kelainan refraksi (ametropia) dapat diakibatkan adanya kelainan axial length atau daya refraksi mata. Pada anak, gangguan refraksi menjadi salah satu penyebab kebutaan terbesar tanpa adanya perhatian dari keluarga. Penelitian ini bertujuan untuk mendapatkan gambaran umum kelainan refraksi mata pada anak. Jenis penelitian ialah literature review. Pencarian data didapatkan dari Google Search, ClinicalKey dan Google Scholar. Seleksi data berdasarkan kriteria inklusi dan ekslusi, dan didapatkan 10 literatur yang terdiri dari 2 case control dan 8 studi potong lintang. Hasil penelitian mendapatkan bahwa kelainan refraksi pada anak berupa miopia, hipermetropia, dan astigmatisma yang meningkat bukan hanya di Indonesia. Kelainan refraksi pada anak digolongkan berdasarkan jenis kelamin dan usia dengan kelainan yang berbeda-beda. Setiap anak dilakukan pemeriksaan dengan menggunakan baku emas. Simpulan penelitian ini ialah kelainan refraksi pada anak dapat berupa miopia, hipermetropia, dan astigmatisma. Tidak terdapat perbedaan bermakna antara jenis kelamin laki-laki dan perempuan. Penelitian pada anak dilakukan pada berbagai golongan usia mulai dari sekolah dasar sampai sekolah menengah. Kelainan refraksi dapat pula terjadi berdasarkan aktivitas yang dilakukan anak sehingga perhatian dari keluarga sangat dibutuhka.Kata kunci: kelainan refraksi, anak